Biochemical Markers of Lipid Profiles Alterations in Children of Baghdad with Recurrent Giardia lamblia Infections - Ali, Lubna Hussain; Hasan, Dhuha Sabah; Jebur, Lina Adil; Salman, Alea Farhan; Abdullah, Hashim J. (American Journal of Biology and Natural Sciences, 2025)
Giardiasis is one of the essential parasitic intestinal diseases, widespread in many countries. Children are the most affected by this disease. The current study aims to see how Giardia lamblia affect on lipid profile. From November 2023 to May 2024, this study was done in Baghdad. The participants in the study were 100 children of both sexes. Based on stool examination, the children were separated into two groups: infected with Giardia lamblia (n=50) and healthy (n=50). The study results indicate that giardiasis infection, particularly recurrent infection, clearly affects lipid metabolism in children. A significant decrease in triglyceride, HDL, and LDL levels (P < 0.001), as well as VLDL levels (P = 0.03 and P = 0.05) was observed with the frequency of infection, indicating impaired fat absorption or transport resulting from damage to the intestinal villi. While no significant differences were observed in total cholesterol between patients and controls with a first-time infection and two-time infection (P = 0.18 and P = 0.69), but significant differences were noted in one infected case (P = 0.04), there was an upward trend in their levels with repeated infection, which may be attributed to chronic inflammatory processes. These results support the hypothesis that giardia disrupts lipid biomarkers and also affects the body’s lipid balance, especially in cases of recurrent infection.